Envenomations caused by fish in Brazil: an evolutionary, morphological, and clinical vision of a neglected problem - Vidal Haddad Junior; Mônica Lopes-Ferreira (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Venomous fish are commonly found in Brazilian waters. The most important marine venomous fish species are stingrays (Dasyatidae, Gimnuridae, Myliobatidae, and Rhinopteridae families), catfish (Ariidae family), scorpionfish and lionfish (both Scorpaenidae family), and toadfish (Batrachoididae family). Meanwhile, Potamotrygonidae stingrays and Pimelodidae catfish are the most important venomous freshwater fish. The mechanisms of envenomation vary and involve various venomous apparatuses and glands. Despite not being highly developed, these venomous apparatuses in fish appear rudimentary, using structures such as fins and rays to inoculate toxins and rarely presenting with specialized structures. Toxins are produced by glandular tissue made up of proteinaceous cells, lacking true glands, and are positioned along the inoculation structures. However, systemic manifestations are rare. No antivenom serum has been developed for any species of American venomous fish. Brazilian venomous fish and their venoms have only recently attracted attention, leading to new studies not only addressing clinical issues in humans, but also exploring the discovery of new active substances with immense pharmacological potential.